Influence of Long Term Application of Green Manure on the Productivity of Coconut Cultivated in Reddish Brown Latosolic Soils in Sri Lanka - Senarathne, S. H. S. (CORD, 2017)
Organic matter contributes in maintaining soil fertility in agriculture. Green leaf biomasses of Gliricidia sepium and Tithonia diversifolia are high in plant nutrients and recognized as potential green manure sources for many crops. In a field experiment carried out in a coconut plantation with Reddish Brown Latosolic soil, two green manure crops were grown to study their abilities and establishment in coconut avenues and to evaluate their effect on nut yield. In situ green manuring, especially with legumes, had the most beneficial effect on soil improvement. The use of green biomass alone has improved soil properties. The biomasses of Gliricidia and Tithonia decomposed rapidly after application to the soil, and incorporated biomass would be an effective source of N, P and K for crops. Results showed that, coconut yields were significantly increased with the incorporation of green biomass of Gliricidia and Tithonia than with commercial inorganic fertilizer application. Mean nut yield for five years in the green manure applied plots was (37-46%) significantly (P < 0.05) higher, compared to that of the inorganic fertilizer applied plots towards the latter part of the experiment. Addition of green manure has significantly (P < 0.05) improved the soil parameters i.e. soil N (by 75%), organic C content (by 86%) and soil microbial activity (by 52%). Soil bulk density has been reduced by 20% which enhances the root growth. The improvement of soil moisture content by 92% is of great importance for coconut in withstanding the frequent dry spells which are on increasing trend with the present climatic change situations. There was no significant effect of green manures on soil pH and P but P content was improved with the use of green biomasses of Gliricidia and Tithonia.